Literature Study: Comparison of Traditional Banking Services and Fintech in Providing Access to Financing for MSMEs - Mahyuzar , Heri; Nugraheni, Anggit Gusti (Amkop Management Accounting Review (AMAR), 2025)
MSMEs still face major obstacles in accessing financing, which is a major factor in supporting their growth and development. The availability of easy and fast access to financing is one of the main keys to advancing the MSME sector, but until now, this access has not been optimal. This study aims to compare the effectiveness of traditional banking and fintech services in providing access to financing for MSMEs. This study uses a qualitative approach with a literature study method. The data used comes from scientific journal articles, OJK and banking publications, news, online articles from credible sources. The data collected was then analyzed using a comparative analysis method between traditional banking and fintech services. The results of the study show that fintech and traditional banking services have their respective advantages and disadvantages in providing access to financing for MSMEs. Fintech excels in speed, inclusiveness, and technological innovation, while conventional banks are stronger in terms of regulation and security. The combination of these two approaches is very important to expand access to financing for MSMEs nationally